PENGARUH LEVERANGE DAN KEPEMILIKAN PUBLIK TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DENGAN MENGGUNAKAN ISR INDEX : (Perusahaan Sub Sector Batu Bara yang terdaftar di Bursa Efek Indonesia Tahun 2019-2021) - Wahyu Ananda Putra; Youdhi Prayogo; Muthmainnah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
This research is entitled The Influence of Leverange and Public Ownership on Disclosure of Corporate Social Responsibility Using the ISR Index (Coal Sub Sector Companies listed on the Indonesia Stock Exchange 2019-2021). The aims of this research are: 1) Want to know the simultaneous influence of leverage and public ownership on Corporate Social Responsibility disclosure. 2) Want to know the partial effect of leverage on Corporate Social Responsibility disclosure. 3) Want to know the partial influence of Public Ownership on Corporate Social Responsibility disclosure. The research method used by researchers is a quantitative approach. The results of this research are: 1) Leverage has no significant effect on the ISR of Coal Sub Sector Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This is shown by the calculated t value being smaller than the t table and the significance level being greater than 0.05, thus indicating that Leverage has no significant effect on the ISR of Coal Sub Sector Companies listed on the Indonesia Stock Exchange in 2019-2021. 2) Public Ownership has a negative effect on the ISR of Coal Sub Sector Companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This is indicated by the calculated t value being smaller than the t table and the significance level being greater than 0.05, with the coefficient being negative. So it shows that Public Ownership has a negative effect on the ISR of Coal Sub Sector Companies listed on the Indonesia Stock Exchange in 2019-2021. 3) The Leverage and Public Ownership variables simultaneously have no significant effect on the ISR of Coal Sub Sector Companies listed on the Indonesia Stock Exchange. This is indicated by the calculated F value being smaller than the F table and the significance level being greater than 0.05, thus indicating that the variables Leverage (X1) and Public Ownership (X2) simultaneously have no significant effect on the ISR of Coal Sub Sector Companies. listed on the Indonesian Stock Exchange in 2019-2021. Meanwhile, the coefficient of determination (R2) reached 0.038 or 3.8%. This means that the Leverage (X1) and Public Ownership (X2) variables influence ISR (Y), with an influence level of 3.8%, and the remaining 96.2% is influenced by other factors.